Fire Losses in the Slovak Republic – Their Classification and Quantification - Klucka, Jozef; Mozer, Vladimir; Dvorsky, Jan (Communications - Scientific letters of the University of Zilina, 2015)
The paper deals with approaches to fire loss classification and quantification. Direct and indirect loss, total loss per fire and the relation of direct and indirect loss to the gross domestic product (GDP) are calculated. Furthermore, the Statgraphics Centurion XV package is used to express: total loss prediction for selected probabilities and probabilities for selected total fire loss values. The results are discussed and conclusions drawn in form of recommendations for the Fire & Rescue Services management in the Slovak Republic.